2013
DOI: 10.1515/jelf-2013-0018
|View full text |Cite
|
Sign up to set email alerts
|

An inquiry into Chinese learners' English-learning motivational self-images: ENL learner or ELF user?

Abstract: This paper reports on findings of a qualitative study that aimed to explore the relevance of English as a Lingua Franca (ELF) to English Language Teaching (ELT) practices by closely examining Chinese learners' English learning from the perspective of the L2 Motivational Self System. Three semi-structured interviews were conducted during an academic year to probe into eight Chinese university students' situated experiences of learning and using English in their life context. Qualitative data analysis revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…It is not difficult to come up with a sound justification for this rather negative and contradictory evaluation of their own English accents on the part of the respondents. As Zheng (2013) observed that most students in China still label themselves as "perennial and error-prone ENL learners" other than rightful English language users, not surprisingly NES accent models are regarded as their ultimate goals of their endeavors and their default reference points albeit Volume 20(1), February 2020February http://doi.org/10.17576/gema-2020February -2001 eISSN: 2550-2131 ISSN: 1675-8021 "unrealistic and unattainable in their locale" (Ibid.). In other words, English in this case was still perceived as a foreign language by a considerable majority of the respondents, though it is against the fact that English for now has been widely employed as an auxiliary language, a lingua franca, possessing regional characteristics and emotive values (Hashim, Kaur & Kuang, 2016), and it also blindfolds the emerging ELF reality at the research site where a growing proportion of communications by means of English were conducted between NNESs in the absence of NESs.…”
Section: Attitudes Toward Respondents' Own English Accentsmentioning
confidence: 99%
“…It is not difficult to come up with a sound justification for this rather negative and contradictory evaluation of their own English accents on the part of the respondents. As Zheng (2013) observed that most students in China still label themselves as "perennial and error-prone ENL learners" other than rightful English language users, not surprisingly NES accent models are regarded as their ultimate goals of their endeavors and their default reference points albeit Volume 20(1), February 2020February http://doi.org/10.17576/gema-2020February -2001 eISSN: 2550-2131 ISSN: 1675-8021 "unrealistic and unattainable in their locale" (Ibid.). In other words, English in this case was still perceived as a foreign language by a considerable majority of the respondents, though it is against the fact that English for now has been widely employed as an auxiliary language, a lingua franca, possessing regional characteristics and emotive values (Hashim, Kaur & Kuang, 2016), and it also blindfolds the emerging ELF reality at the research site where a growing proportion of communications by means of English were conducted between NNESs in the absence of NESs.…”
Section: Attitudes Toward Respondents' Own English Accentsmentioning
confidence: 99%
“…From the perspective of Global Englishes (GE), it is necessary to critically evaluate the current educational materials used in pronunciation teaching in China to further investigate the 'gap' between language teaching and language practice, and also to understand language learners' pragmatic needs of language learning (cf. Galloway & Rose 2015;Sung 2015;Wang 2013;Zheng 2013). In what follows, I shall move to my research context, a medium-sized university located in southeast China.…”
Section: Researching China English Accentsmentioning
confidence: 99%
“…At this point, the function and role of English is a lot more than just a subject, it is a tool to bridge the communication between China and other nations. As a prove of the shift from EFL to ELF, Zheng's (2013) study shows that there is an extensive ELF interaction taking place during Beijing Olympic Games as the volunteer in the event revealed. Furthermore, the growth of schools employing English as Medium of Instruction (EMI) had doubled from 260 in 2003 to 500 in 2010 and is believed to keep increasing (Hu & Alsagoff, 2010).…”
Section: Introductionmentioning
confidence: 89%